MODIFIKASI RAK PENYIMPANAN FREON ERGONOMIS DENGAN MENGGUNANKAN METODE VDI 2221 - Calvin; Daywin, Frans Jusuf; Andres (Jurnal Mitra Teknik Industri, 2023)
PT. Wijaya Anugerah Abadi is a company engaged in services related to air conditioners both in terms of installation, removal and maintenance. This company serves from the aspect of sales, installation, service, and repair for all the needs of individuals, offices, factories, etc. Companies need many types of freon tubes to support their work. Storage of freon tubes when aligned below is very space-consuming and makes it difficult for technicians to identify the type of freon tube because several freon tubes have the same color, therefore in this study the authors are trying to make a freon tube storage rack which is expected to make it easier for technicians to identify the type of tube freon is needed, besides that this storage rack is expected to increase the space efficiency of the company. Data collection and processing includes several things, namely respondent data, product prerequisite questions and product research questions. The questionnaire is intended to obtain respondent data in using the tool you want to design. Then, the use of the Nordic Body Map questionnaire aims to determine work discomfort felt by workers. The researcher will continue the design according to the company's needs. using the VDI 2221 method. Based on the results of observations and interviews with workers, it can be concluded that there are still many physical complaints experienced by workers, so this research is focused on reducing workers' physical complaints. The design of the Freon tube storage rack designed in this study is aimed at reducing the physical complaints of workers in picking up and storing freon tubes.